A dystroglycan mutation (p.Cys667Phe) associated to muscle‐eye‐brain disease with multicystic leucodystrophy results in ER‐retention of the mutant protein. Issue 2 (7th December 2017) - Signorino, Giulia; Covaceuszach, Sonia; Bozzi, Manuela; Hübner, Wolfgang; Mönkemöller, Viola; Konarev, Petr V.; Cassetta, Alberto; Brancaccio, Andrea; Sciandra, Francesca
Abstract: Dystroglycan (DG) is a cell adhesion complex composed by two subunits, the highly glycosylated α‐DG and the transmembrane β‐DG. In skeletal muscle, DG is involved in dystroglycanopathies, a group of heterogeneous muscular dystrophies characterized by a reduced glycosylation of α‐DG. The genes mutated in secondary dystroglycanopathies are involved in the synthesis of O‐mannosyl glycans and in the O‐mannosylation pathway of α‐DG. Mutations in the DG gene ( DAG1 ), causing primary dystroglycanopathies, destabilize the α‐DG core protein influencing its binding to modifying enzymes. Recently, a homozygous mutation (p.Cys699Phe) hitting the β‐DG ectodomain has been identified in a patient affected by muscle‐eye‐brain disease with multicystic leucodystrophy, suggesting that other mechanisms than hypoglycosylation of α‐DG could be implicated in dystroglycanopathies. Herein, we have characterized the DG murine mutant counterpart by transfection in cellular systems and high‐resolution microscopy. We observed that the mutation alters the DG processing leading to retention of its uncleaved precursor in the endoplasmic reticulum. Accordingly, small‐angle X‐ray scattering data, corroborated by biochemical and biophysical experiments, revealed that the mutation provokes an alteration in the β‐DG ectodomain overall folding, resulting in disulfide‐associated oligomerization. Our data provide the first evidence of a novel intracellular mechanism, featuring an anomalous endoplasmic reticulum‐retention, underlying dystroglycanopathy. Abstract : Dystroglycan (DG) is a cell adhesion complex composed by two subunits, α‐ and β‐DG. DG is involved in dystroglycanopathies, a group of heterogeneous muscular dystrophies. Recently, a homozygous mutation (p.Cys699Phe) has been identified in a patient affected by severe muscular dystrophy. Herein, we have characterized the DG mutant and we observed that the mutation alters the DG processing leading to its retention in the endoplasmic reticulum. Our data suggest a novel intracellular mechanism, featuring an anomalous endoplasmic reticulum‐retention, underlying dystroglycanopathy.